Prayer and (Im)Politeness: Reading Psalm 7 - Jones, Ethan (Old Testament essays, 2024)
Politeness is generally understood as culturally bound. Recently, however, scholars have been mining the world’s languages to discover a typology of linguistic politeness. While living languages have been studied extensively, scholars have also begun investigating ancient languages, such as Egyptian and Hittite, for evidence and use of such language. Scholarship on the Hebrew Bible has made some initial steps in this type of study. The research thus far has centred on speeches within Hebrew narrative with little to no attention paid to poetry. This is disappointing as the book of Psalms consists of performative prayers directed to Yhwh. To begin to fill this gap in research, this article highlights the significance of the taxonomy of linguistic politeness in order to bring more clarity to the language of prayer in the Psalms and in Ps 7 in particular.